Relationship between Artificial Intelligence (AI) and Teachers’ Education Programmes for Sustainable National Development in Basic Education in Public Schools of North Central Nigeria - Agwom , Saleh Dauda; Jibrin, Samira Gane; Lawal , Binta Bagiwa (Kashere Journal of Education, 2025)
This study examined the relationship between artificial intelligence (AI) and teachers' education programs for sustainable national development in basic education in public schools in North Central Nigeria, using the National Certificate of Education (NCE) and the Professional Diploma of Education (PDE) as indices. The study explored how AI-driven instructional strategies, adaptive learning systems, and teacher training technologies influence the preparation and professional capacity of pre-service and in-service teachers. A descriptive survey design was adopted to collect data from a population of 58,427 NCE and PDE students, lecturers, and teacher trainers across Colleges of Education and Faculties of Education in the North Central zone. Using Krejcie and Morgan’s table, a sample of 382 respondents was selected. A structured questionnaire, validated by experts with a Content Validity Index (CVI) of 0.83 and a Cronbach Alpha reliability coefficient of 0.79, was administered. Descriptive and inferential statistics, including mean, standard deviation, and Pearson correlation, were used for analysis at a 0.05 significance level. Findings revealed a significant positive relationship between AI integration and the effectiveness of teachers’ education programs in enhancing basic education outcomes. However, challenges such as inadequate digital infrastructure, poor funding, limited AI literacy among teacher educators, and resistance to technological change constrain optimal implementation. The study concludes that the adoption of AI within teacher education programmes is pivotal for sustainable national development through improved teaching quality, innovation, and learning efficiency. It recommends comprehensive digital capacity-building initiatives for NCE and PDE educators and the inclusion of AI-based pedagogical modules in teacher training curricula.